Floristic composition of mangrove community in Ngurah Rai Forest Park and Nusa Lembongan, Bali, Indonesia - I MADE SAKA WIJAYA; I PUTU SUGIANA; IDA AYU ASTARINI; I KETUT GINANTRA; KHAIRUL ADHA A. RAHIM (Society for Indonesian Biodiversity, 2024)
Abstract. Wijaya IMS, Sugiana IP, Astarini IA, Ginantra IK, Rahim KAA. 2024. Floristic composition of mangrove community in Ngurah Rai Forest Park and Nusa Lembongan, Bali - Indonesia. Biodiversitas 25: 300-309. The floristic composition of mangroves can be influenced by various factors, one of which is the size of the island. In Bali, Ngurah Rai Forest Park is one of the mangrove areas in the mainland of Bali, while Nusa Lembongan on the southeastern mainland represents the mangrove on the small island. This research aimed to study the floristic composition of the mangrove species in Ngurah Rai Forest Park and Nusa Lembongan based on the species diversity and the structure of mangrove community. Based on the explorative method, both locations have 20 true mangrove species cumulatively, with 18 species in Ngurah Rai Forest Park and 15 species in Nusa Lembongan. The mangrove community structure is majorly composed by Sonneratia alba and Rhizophora (R. apiculata, R. mucronata, and R. stylosa) in trees, saplings, and seedlings. Sonneratia alba has more impact in relative dominance, while the Rhizophora has more impact in relative density. Based on the Shannon-Wiener Index of Diversity, the mangrove community status is Moderate in both locations in all growth forms (trees, saplings, and seedlings). The Index of Dominance and Index of Evenness indicates the mangrove community is in stable condition with no extremely dominated species and fairly even species distribution. The mangrove condition is categorized as Good with Dense Trees based on the Decree of the Minister of Environment number 201 of 2004.